2016
DOI: 10.1073/pnas.1613910113
|View full text |Cite|
|
Sign up to set email alerts
|

Chilling-induced tomato flavor loss is associated with altered volatile synthesis and transient changes in DNA methylation

Abstract: Commercial tomatoes are widely perceived by consumers as lacking flavor. A major part of that problem is a postharvest handling system that chills fruit. Low-temperature storage is widely used to slow ripening and reduce decay. However, chilling results in loss of flavor. Flavor-associated volatiles are sensitive to temperatures below 12 °C, and their loss greatly reduces flavor quality. Here, we provide a comprehensive view of the effects of chilling on flavor and volatiles associated with consumer liking. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
175
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(188 citation statements)
references
References 49 publications
5
175
1
1
Order By: Relevance
“…Indeed, many changes in gene expression were not correlated with the corresponding methylation changes in this study (Figure b and c). Similar results were also observed in tomato fruit under chilling stress, revealing that only 37%–67% of different GO term genes presented a negative correlation between methylation level and transcript abundance (Zhang et al ., ). This phenomenon was partly caused by methylation alterations that did not affect gene expression in some regions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, many changes in gene expression were not correlated with the corresponding methylation changes in this study (Figure b and c). Similar results were also observed in tomato fruit under chilling stress, revealing that only 37%–67% of different GO term genes presented a negative correlation between methylation level and transcript abundance (Zhang et al ., ). This phenomenon was partly caused by methylation alterations that did not affect gene expression in some regions.…”
Section: Discussionmentioning
confidence: 97%
“…Paper bagging (environmental factor changes) altered the DNA methylation and histone modifications on MdMYB1 and activated the MdMYB1 gene and downstream genes, leading to differential anthocyanin pigmentation (Bai et al ., ). Cold storage of tomato increased methylation of RIN (RIPENING INHIBITOR) and decreased the transcripts of RIN and some of its direct targets (Zhang et al ., ). Compared with regulating structural genes, it is understandable that plants prefer a more energy‐saving and high‐efficient way of controlling TFs to further regulate biological pathways in response to environmental influences.…”
Section: Discussionmentioning
confidence: 97%
“…Libraries for high-throughput Illumina strand-specific RNA-seq were prepared as described previously (Zhang et al, 2016). Three biological replicates for various organs, fruit development and ripening stages and treatment were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence has recently emerged that, in addition to ethylene and the TFs, DNA methylation is another key regulator of fruit ripening (27). Furthermore, a recent study revealed that DNA methylation is associated with chilling-induced flavor loss in tomato fruits (28). Tomato fruits undergo a dramatic loss in DNA methylation during ripening (27).…”
mentioning
confidence: 99%